Persistence in Problematic Internet Use—A Systematic Review and Meta-Analysis - Dahl, Daniel; Bergmark, Karin Helmersson (Frontiers in Sociology, 2020)
Background and aims. Problematic internet use, internet addiction and internet gaming disorder all describe a global phenomenon where individuals have trouble limiting their use of computers to such an extent that their use has negative consequences. Past systematic reviews and meta-analyses have focused on estimating prevalence, but there has been no comprehensive research synthesis of the trajectory of the problem. The objective was to create a pooled estimate of the persistence of problematic internet use. This review included studies using a longitudinal panel data design with a follow-up of at least a year. Studies had to be published before the end of the year 2017, in peer-reviewed academic journals, using English language. Samples from populations in any country were accepted, given they were of acceptable quality. Methods. A literature search was conducted in Web of Science, Pro Quest and Scopus. Several definitions of problematic internet use were included. Inverse-variance, random-effect meta-analysis was used to estimate weighted summary means of persistence. Attrition and selection bias were investigated using pre-specified tools, and heterogeneity was assessed in subgroup analysis. Results. Nine studies fit the criteria, all using samples from Asian or Western countries. The aggregate estimate for 1-year persistence it was 50% (CI: 40-61%), but results were heterogeneous. Prevalence and persistence estimates were correlated, and generally higher in Asian countries. Methodological differences only explain part of the heterogeneity. Conclusion. All included studies found individuals with persistent problems, but the between-studies variation is substantial.